Excellence Of The Quality Tools And Their Application: The Quality Professionals’ Perspective - Patil, Avesh; Shamsher, Salim; Basu, Analjyoti (Greenation International Journal of Engineering Science, 2024)
Quality tools are the ones that give cutting edge to the process or business. It carries remarkable weightage when it comes to the deliverables. A proper use of quality tool can provide break through improvements in quality, efficiency and the business results. The selection of such tools hence is very important. However, in spite of the importance the tools used may not be on the merit and may just get into place by a single person’s opinion or a trend or the thing in vogue or based on what the peers and competitors are using. Some times that tools are used only to show that it is part of their stable. This sorry state of selection is very common and companies end up paying hefty amounts for tool that are not good for them and are just a part of the introduction page of the organization. This paper is based on the study of the tools, their usage and their perceive benefits to assign a number to the tool that will tell the unitality or goodness of the tool for the purpose. There is not recommendation of a single tool for a purpose but it gives you a range of tools and range of alternatives that the user need to select from so that the purpose is met. The paper has two distinct parts, one sharing the name of the tools and their usage so that the user is aware what they are looking at and the other part is about the utility of these tools basically for improving quality of the product or process. Whever rating is done, the assessor needs to be well versed with the entity. Since there are quite a few tools considered here, it becomes very challenging to get right juries or assessors to rate the tools. However, thanks to the development of the Automobile Industry over past 140 odd years, which uses most of the tools under consideration, there are ample number of professionals who authoritatively can comment about the goodness of the tools. For this paper these were the group of elite professionals who were contacted. These are head of the department of quality, holding positions like President, Vice president, Directors, Senior General Mangers and so on. There were other senior professionals like Six Sigma Master Black Belt, Black Belts from reputed agencies like American Society of Quality (ASQ) and likes. most of these professionals were from Automobile OE manufacturers producing Cars, Trucks, Tractors & Farm Equipments, Two wheelers and Engine manufacturers. Based on their experience they rated these tools in 1 to 10 scale, 10 being the ones having most significant effect on quality improvement efforts and 1 being very low effect on quality improvement. The output of the research is in the form of a number assigned to the tool that tells about how effective this tool is in relation to the efforts to improve quality. Higher the number better the tool for the purpose.